COVID‐19 in vaccinated versus unvaccinated hematologic malignancy patients. Issue 6 (16th August 2022) - DeVoe, Catherine; Pandey, Shraddha; Shariff, Dayana; Arora, Shagun; Henrich, Timothy J.; Yokoe, Deborah S.; Langelier, Charles R.; Servellita, Venice; Chiu, Charles; Miller, Steve; Babik, Jennifer M.; Chin‐Hong, Peter; et al.
Abstract: The effect of vaccination on severity of subsequent COVID‐19 in patients with hematologic malignancies (HMs) is unknown. In this single‐center retrospective cohort study, we found no difference in severity of COVID‐19 disease in vaccinated ( n = 16) versus unvaccinated ( n = 54) HM patients using an adjusted multiple logistic regression model. Recent anti‐B‐cell therapy was associated with more severe illness. Abstract :